2000
DOI: 10.1136/jnnp.69.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Camino(R) intracranial pressure monitor: prospective study of accuracy and complications

Abstract: Objectives-The fibreoptic device is a type of intracranial pressure monitor which seems to oVer certain advantages over conventional monitoring systems. This study was undertaken to analyse the accuracy, drift characteristics, and complications of the Camino® fibreoptic device. Methods-One hundred and eight Camino® intracranial pressure (ICP) devices, in their three modalities, were implanted during 1997. The most frequent indication for monitoring was severe head injury due to road traYc accidents. Results-Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 23 publications
0
60
0
4
Order By: Relevance
“…In a 1997 series of 108 intraparenchymal devices, the rate of infection was 2.9% and the rate of intracranial hemorrhage was 2.1% (15.3% in patients with coagulopathies). 191 Two of 22 patients (9%) patients in the placebo arm of a trial of intraventricular thrombolysis developed ventriculitis, but these patients had multiple intrathecal injections, which could potentially increase the risk of infection. 184 Before insertion of a monitoring device, the patient's coagulation status should be evaluated.…”
mentioning
confidence: 99%
“…In a 1997 series of 108 intraparenchymal devices, the rate of infection was 2.9% and the rate of intracranial hemorrhage was 2.1% (15.3% in patients with coagulopathies). 191 Two of 22 patients (9%) patients in the placebo arm of a trial of intraventricular thrombolysis developed ventriculitis, but these patients had multiple intrathecal injections, which could potentially increase the risk of infection. 184 Before insertion of a monitoring device, the patient's coagulation status should be evaluated.…”
mentioning
confidence: 99%
“…Constituye un método relativamente sencillo, seguro 14,16,17,21 y que aporta una valiosa información. En algunos trabajos, se utiliza el registro de PIC para evaluar fundamentalmente la presión media, sin atender excesivamente a la morfología del trazado 13 .…”
Section: Discussionunclassified
“…The hemorrhagic complication is observed in 2.8% of the cases, and the incidence of bacterial colonization has been brought down to 0-14% of the cases [5][6][7] . In a prospective study of intraparenchymal monitoring, haemorrhage was observed in 2.1% of patients without alteration of the coagulation, and in 15.3% of their counterparts with coagulopathy 8 . In another study, 118 patients with intracranial pathology but without coagulopathy were evaluated, and the incidence of observed complications was: infection (0.7%), intraparenchymal haematoma (5.1%) and complications related with technical aspects (23.5%) 9 .…”
Section: Discussionmentioning
confidence: 99%